PENYESUAIAN PSIKOLOGIS ORANGTUA DENGAN ANAK DOWN SYNDROME - Ni Made Diah Ayu Anggreni; Tience Debora Valentina (Jurnal Psikologi Udayana, 2015)
Parents wish to have a healthy child, both physically and mentally, but in fact not all couples blessed with healthy children and actually get a child with early developmental disorder, such as down syndrome (Mawardah, Siswati, & Hidayati, 2012). Ravindranadan dan Raju (2008) represent that parents with special needs face a stressor and different stress reactions related to their child disability. To face the stressor and stress resctions, Pozzo, Sarria and Brioso (2011) revealed that parents with disabilities need to make psychological adjustments. This situation attracts researcher to find out the experiences and psychological adjustments of parents with down syndrome child. This study use qualitative method with phenomenological approach. Respondents in this study were eight people, consisting of four fathers and four mothers who lived in Denpasar and Tabanan. The result of this study indicates that parents with down syndrome children are able to make psychological adjustment. There are five factors that influenced parents to make psychological adjustment, there are characteristics of down syndrome child are capable of independent, support and encouragement from the surrounding environment, has a positive perception of the child with down syndrome, using adaptive coping strategies and individual characteristics such as high education. Keywords: psychological adjustment, parent, down syndrome child.